2013
DOI: 10.1371/journal.pone.0074768
|View full text |Cite
|
Sign up to set email alerts
|

C22:0- and C24:0-dihydroceramides Confer Mixed Cytotoxicity in T-Cell Acute Lymphoblastic Leukemia Cell Lines

Abstract: We previously reported that fenretinide (4-HPR) was cytotoxic to acute lymphoblastic leukemia (ALL) cell lines in vitro in association with increased levels of de novo synthesized dihydroceramides, the immediate precursors of ceramides. However, the cytotoxic potentials of native dihydroceramides have not been defined. Therefore, we determined the cytotoxic effects of increasing dihydroceramide levels via de novo synthesis in T-cell ALL cell lines and whether such cytotoxicity was dependent on an absolute incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…We also found an inverse association between VLCSFA and T‐NHL. An in vitro study reported that certain acyl fatty acids, such as 22:0 and 24:0, but not shorter chain acyl fatty acids, are cytotoxic to T cell acute lymphoblastic leukemia cell lines . However, it remains unknown whether a similar effect exists in vivo or would confer protection against developing T‐NHL.…”
Section: Discussionmentioning
confidence: 99%
“…We also found an inverse association between VLCSFA and T‐NHL. An in vitro study reported that certain acyl fatty acids, such as 22:0 and 24:0, but not shorter chain acyl fatty acids, are cytotoxic to T cell acute lymphoblastic leukemia cell lines . However, it remains unknown whether a similar effect exists in vivo or would confer protection against developing T‐NHL.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, C 16 -ceramide promotes head and neck cancer cell proliferation and its increased serum levels associate with a positive lymph node status in breast cancer patients [38, 39]. On the other hand, there are studies showing that C 16 -ceramide is pro-apoptotic, whereas C 24 -ceramide protects from cell death [40, 41]. Thus, overall, distinct roles of ceramides appear to be context dependent, especially that knockout mice for multiple CerS enzymes exhibit different phenotypes: mice that express a mutant CerS1 (toppler mice) exhibit neurological disorders associated mainly with alterations in Purkinjee cells; mice with genetic loss of CerS2 results in liver damage; mice with CerS6 knockout exhibit neurological/behavioral alterations; and CerS4 knockout mice exhibit severe alopecia with alterations in sebaceous glands and sebum contents [42-43,204].…”
Section: Metabolism and Biological Roles Of Ceramidementioning
confidence: 99%
“…Blockade of Des1 produces an increase in dihydroceramides (dhCers), which have emerged as bioactive lipids and the target of several drugs ( 34 ), including fenretinide. Several studies have shown that cells respond to fenretinide treatment with a robust production of dhCers (35)(36)(37)(38)(39)(40)(41)(42)(43)(44), and that this increase induces autophagy ( 45,46 ). Furthermore, experimental evidence exists on the connection between resistance to fenretinide and increased S1P production ( 38,44 ) due to an increased SK activity and SK1 mRNA and protein levels ( 38 ).…”
Section: Des1 Enzyme Assaymentioning
confidence: 99%